A Sentiment Analysis of Free Nutritious Meal Program on Platform X: Comparing Naive Bayes, SVM, Random Forest, and IndoBERT - Alrijal Nur Ilham; Etika Kartikadarma (Journal of Applied Informatics and Computing, 2026)
The Free Nutritious Meal Program (MBG), launched by the Indonesian government in January 2025, generated various public responses on social media, particularly on platform X. This study aims to analyze public sentiment toward the MBG Program and compare the performance of four sentiment classification methods: Naive Bayes, Support Vector Machine (SVM), Random Forest, and IndoBERT. The dataset was collected through tweet crawling using the keywords “MBG” and “Makan Bergizi Gratis” during the period of July–December 2025, resulting in 1,906 Indonesian-language tweets. The preprocessing stage included cleaning, case folding, normalization, tokenization, stopword removal, and stemming. Sentiment labeling was performed using the InSet Lexicon and produced 1,113 negative tweets and 793 positive tweets. Manual validation on part of the dataset was conducted by two independent annotators and achieved a Cohen’s Kappa score of 0.78, indicating substantial agreement. For classical machine learning models, feature extraction was carried out using TF-IDF, while IndoBERT used contextual text representations without stemming. Class imbalance in classical models was handled using SMOTE, whereas IndoBERT applied class weighting. The experimental results show that IndoBERT achieved the best performance with an accuracy of 92.93%. Among the classical models, SVM produced the highest performance with an accuracy of 92.15%, followed by Naive Bayes and Random Forest. Word frequency analysis also revealed that positive sentiment was mainly associated with support for the program and nutrition-related topics, while negative sentiment was dominated by concerns about food safety, budget management, and criticism of the program. Based on the findings, IndoBERT is more effective in understanding the context of Indonesian-language tweets. However, TF-IDF-based classical models, especially SVM, still provide competitive performance with lower computational requirements, making them suitable for sentiment analysis in public policy studies.